Multinational corporations and abusive states: should they stay put and make things better or withdraw? - Fisher, Colin (Henry Stewart Talks, 2011)
The dilemmas, Talisman and Sudan, Yahoo & Google in China, Which states?, Comparing corporations and countries, The options for multinationals, South Africa under Apartheid, The Sullivan Principles, Corporations with sovereign powers, Informal empires, Modes of ethical thinking, Critical questions, Extractive industries, Conclusions, References